Serum uric acid and the risk of cardiovascular and renal disease. Issue 9 (September 2015) - Borghi, Claudio; Rosei, Enrico Agabiti; Bardin, Thomas; Dawson, Jesse; Dominiczak, Anna; Kielstein, Jan T.; Manolis, Athanasios J.; Perez-Ruiz, Fernando; Mancia, Giuseppe
<x xml:space="preserve">Abstract</x> Substantial evidence suggests that chronic hyperuricemia is an independent risk factor for hypertension, metabolic syndrome, chronic kidney disease (CKD) and cardiovascular diseases. This highlights the need for greater attention to serum uric acid levels when profiling patients, and suggests that the threshold above which uricemia is considered abnormal is 6 mg/dl, in light of the available evidence. Another important question is whether lowering serum uric acid can improve cardiovascular and renal outcomes, and what therapeutic mechanism of action could provide more clinical benefits to patients; the available literature shows a trend toward improvement associated with administration of urate-lowering drugs, in particular for the xanthine oxidase inhibitors. The demonstrated efficacy of urate-lowering therapy on outcomes other than gout flares leads to the consideration that treatment may be beneficial even in the absence of overt gout when hyperuricemia accompanies other clinical conditions, such as urate deposition, advanced CKD or cardiovascular risk factors.